A non‐synonymous SNP in exon 3 of the KIT gene is responsible for the classic grey phenotype in alpacas (Vicugna pacos). (12th July 2019) - Jones, M.; Sergeant, C.; Richardson, M.; Groth, D.; Brooks, S.; Munyard, K.
Summary: The alpaca classic grey phenotype is of particular interest to the industry. Until now, there were only indirect data suggesting that the KIT gene was involved in the classic grey phenotype. All exons of KIT in three black and three classic silvergrey alpacas were sequenced. Five non‐synonymous SNPs were observed. There was only one SNP found that was present only in the silvergrey alpacas, and this was also the only SNP predicted to be damaging. This variant results in a change of a glycine (Gly) to an arginine (Arg) at amino acid position 126 (c.376G>A), occurring in the second Ig‐like domain of the extracellular domain of KIT . Basic protein modelling predicted that this variant is likely destabilising. Therefore, an additional 488 alpacas were genotyped for this SNP using the tetra‐primer amplification refractory mutation system PCR (Tetra‐primer ARMS‐PCR). All classic grey alpacas were observed to be heterozygous, and 99.3% of non‐grey dark base colour alpacas were found to be homozygous for the wildtype allele in this position. These results confirm that the classic grey phenotype in alpacas is the result of a c.376G>A (p.Gly126Arg) SNP in exon 3 of KIT . These data also support the hypothesis that the grey phenotype is autosomal dominant and that the mutation is most likely homozygous lethal.